Use planning analysis on agricultural holdings according to their physical size: Case study - Mihaela Cristina Vlad (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The processes of planning of the production activity of agricultural holdings are, in fact, a number of activities to study the alternatives and choose the optimal Variant. It is conducted on the basis of the theory of planning by the manager/administrator and seeks to provide for a high efficiency of work, to develop and refine the tools, techniques and levers for the conduct of competition on the market, to reduce the uncertainty, to ensure management and control instruments in crisis situations, etc.
Keywords: 330; the production plan; marketing plan; business plan